Pembentukan Komunitas Remaja Peduli Stroke Di Desa Grimak Kecamatan Narmada Kabupaten Lombok Barat Provinsi Nusa Tenggara Barat - Nursukma P, Dewi; Romadonika, Fitri; Oktaviani, Elisa; Putri Rusiana, Harlina; Adithia P, Eka; Arifin, Zaenal; Nurul Hidayati, Baiq; Pratiwi Safitri, Rias (Jurnal LENTERA, 2021)
The rapid development of technology and information today has had a significant impact on changes in people's behavior. Changes in behavior are often the main cause of the emergence of various types and forms of health problems, such as the high morbidity caused by Non-Communicable Diseases (PTM). One of the PTM which is a very serious health problem today is stroke. The purpose of this activity is to increase public awareness of the prevention of stroke disease through the formation of a community for teenagers who care about stroke. The method used in this activity is to form a youth community to have an activity plan oriented to the early prevention of Stroke. The people who are the targets in this activity are people in Grimak Indah Village, Narmada District, West Lombok Regency, West Nusa Tenggara Province who are at risk of having a stroke. After the implementation of this service activity, it is hoped that it can increase public knowledge and awareness of the early prevention of Stroke